Mister Exam
Lang:
EN
EN
ES
RU
Other calculators:
Integral Step by Step
Derivative Step by Step
Differential equations Step by Step
How to use it?
Limit of the function
:
Limit of -1/(-3+x)+6/(-9+x^2)
Limit of (5+x-3*x^2)/(4-x+2*x^2)
Limit of -2+5*x+14*x^2/3
Limit of ((-1+5*x^2)/(-1+7*x^2))^(1+5*x)
Integral of d{x}
:
e^(-x)/sqrt(x)
Identical expressions
e^(-x)/sqrt(x)
e to the power of ( minus x) divide by square root of (x)
e^(-x)/√(x)
e(-x)/sqrt(x)
e-x/sqrtx
e^-x/sqrtx
e^(-x) divide by sqrt(x)
Similar expressions
e^(x)/sqrt(x)
Limit of the function
/
e^(-x)/sqrt(x)
Limit of the function e^(-x)/sqrt(x)
at
→
Calculate the limit!
v
For end points:
---------
From the left (x0-)
From the right (x0+)
The graph:
from
to
Piecewise:
{
enter the piecewise function here
The solution
You have entered
[src]
/ -x \ | e | lim |-----| x->oo| ___| \\/ x /
lim
x
→
∞
(
e
−
x
x
)
\lim_{x \to \infty}\left(\frac{e^{- x}}{\sqrt{x}}\right)
x
→
∞
lim
(
x
e
−
x
)
Limit(1/(E^x*(sqrt(x))), x, oo, dir='-')
Lopital's rule
There is no sense to apply Lopital's rule to this function since there is no indeterminateness of 0/0 or oo/oo type
The graph
0
2
4
6
8
-8
-6
-4
-2
-10
10
0
5
Plot the graph
Other limits x→0, -oo, +oo, 1
lim
x
→
∞
(
e
−
x
x
)
=
0
\lim_{x \to \infty}\left(\frac{e^{- x}}{\sqrt{x}}\right) = 0
x
→
∞
lim
(
x
e
−
x
)
=
0
lim
x
→
0
−
(
e
−
x
x
)
=
−
∞
i
\lim_{x \to 0^-}\left(\frac{e^{- x}}{\sqrt{x}}\right) = - \infty i
x
→
0
−
lim
(
x
e
−
x
)
=
−
∞
i
More at x→0 from the left
lim
x
→
0
+
(
e
−
x
x
)
=
∞
\lim_{x \to 0^+}\left(\frac{e^{- x}}{\sqrt{x}}\right) = \infty
x
→
0
+
lim
(
x
e
−
x
)
=
∞
More at x→0 from the right
lim
x
→
1
−
(
e
−
x
x
)
=
e
−
1
\lim_{x \to 1^-}\left(\frac{e^{- x}}{\sqrt{x}}\right) = e^{-1}
x
→
1
−
lim
(
x
e
−
x
)
=
e
−
1
More at x→1 from the left
lim
x
→
1
+
(
e
−
x
x
)
=
e
−
1
\lim_{x \to 1^+}\left(\frac{e^{- x}}{\sqrt{x}}\right) = e^{-1}
x
→
1
+
lim
(
x
e
−
x
)
=
e
−
1
More at x→1 from the right
lim
x
→
−
∞
(
e
−
x
x
)
=
−
∞
i
\lim_{x \to -\infty}\left(\frac{e^{- x}}{\sqrt{x}}\right) = - \infty i
x
→
−
∞
lim
(
x
e
−
x
)
=
−
∞
i
More at x→-oo
Rapid solution
[src]
0
0
0
0
Expand and simplify
The graph